Decision Rules for Corporate Investment - Reinier de Adelhart Toorop; Dirk Schoenmaker; Willem Schramade (International Journal of Financial Studies, 2024)
We investigate the decision rules for corporate investment by designing a company value frontier. This company value frontier allows for balancing the financial value and social and environmental impacts. This article develops novel value concepts—ranging from shareholder value to shareholder welfare and integrated value—resulting in varying preferences for social and environmental impacts or values. Next, these preferences are incorporated in investment decision rules. The traditional net present value (NPV) rule optimises only the financial value. We propose a new integrated present value (IPV) decision rule that includes a preference for social and environmental values without neglecting the financial value. By applying the new IPV rule, responsible companies are able to achieve more sustainable outcomes.